Associations Between ADHD Symptoms and Occupational, Interpersonal, and Daily Life Impairments Among Pregnant Women. Issue 9 (July 2019) - Eddy, Laura D.; Jones, Heather A.; Snipes, Daniel; Karjane, Nicole; Svikis, Dace
Objective: Past research links symptoms of depression and anxiety with functional impairments among pregnant women. However, no prior research has examined the impact of ADHD symptoms among this population. The current study examines associations between ADHD symptoms and impairment in several life domains.Method: Self-report measures of ADHD symptoms, impairment, and demographic information were collected from 250 pregnant women at an urban women's health clinic in the Southeast. Data were assessed using multivariate path analysis.Results: Inattentive symptoms were significant predictors of professional life impairment, daily life impairment, and relationship impairment. Impulsivity uniquely predicted variability in professional life impairment and relationship impairment. Hyperactivity was not a significant predictor.Conclusion: Future research should focus on the mechanisms by which inattention and impulsivity affect daily functioning in pregnant women, in addition to investigating potential interventions. Health care professionals should assess for impulsivity and inattention among pregnant women.